Reduction of the incidence of neuroma formation by proximal epineural stripping - Yildirim, A. M.; Okur, M. I.; Ozveren, F.; Ozercan, R. (Churchill Livingstone, 2006)
The effect of proximal epineural stripping on neuroma formation was studied in the peroneal nerve stumps of the rat. After transection of the peroneal nerve, the epineurium of the proximal stump was stripped back by 6 to 8 mm and the nerve fascicles left uncovered in the study group. The transected nerve was left untreated in the control group. All nerves were evaluated by light microscopy 6 months after the operation. Two neuromas occurred in 20 stumps after epineural stripping while 15 neuromas occurred in the control group. Based on histological data, we conclude that stripping of the epineurium may inhibit neuroma formation in the rat.
Keywords: neuroma; proximal epineural stripping; epineurium; rat